High levels of SOX5 decrease proliferative capacity of human B cells, but permit plasmablast differentiation - Rakhmanov, Mirzokhid; Sic, Heiko; Kienzler, Anne-Kathrin; Fischer, Beate; Rizzi, Marta; Seidl, Maximilian; Melkaoui, Kerstina; Unger, Susanne; Moehle, Luisa; Schmit, Nadine E.; Deshmukh, Sachin D.; Ayata, Cemil Korcan; et al. (PLoS ONE, 2014)
Currently very little is known about the differential expression and function of the transcription factor SOX5 during B cell maturation. We identified two new splice variants of SOX5 in human B cells, encoding the known L-SOX5B isoform and a new shorter isoform L-SOX5F. The SOX5 transcripts are highly expressed during late stages of B-cell differentiation, including atypical memory B cells, activated CD21low B cells and germinal center B cells of tonsils. In tonsillar sections SOX5 expression was predominantly polarized to centrocytes within the light zone. After in vitro stimulation, SOX5 expression was down-regulated during proliferation while high expression levels were permissible for plasmablast differentiation. Overexpression of L-SOX5F in human primary B lymphocytes resulted in reduced proliferation, less survival of CD138neg B cells, but comparable numbers of CD138+CD38hi plasmablasts compared to control cells. Thus, our findings describe for the first time a functional role of SOX5 during late B cell development reducing the proliferative capacity and thus potentially affecting the differentiation of B cells during the germinal center response.
EVALuna2:13622